Training on making liquid organic fertilizer from tofu whey waste to reduce environmental pollution - Siti Harnina Bintari; Lina Herlina; Dimas Wicaksono; Sunyoto; Sisilia Prita Dewi Purnamaningrum; Wildan Dwija Laksana; Berlina Maika Ulfa (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The utilization of tofu whey waste is crucial due to its environmental impact and the lack of proper waste management by tofu and tempeh producers in Tengaran, Salatiga. Currently, liquid waste is still discharged into nearby water bodies, affecting both the environment and surrounding agricultural areas. These areas are dominated by rice fields where farmers heavily rely on chemical fertilizers such as Urea and Ponska. This community service program aims to convert tofu and tempeh liquid waste into liquid organic fertilizer (LOF) to reduce chemical fertilizer usage and minimize environmental pollution. The implementation involved training and mentoring members of the Barukan Farmer Group (Poktan Barukan) in LOF production through simple biotechnological methods. The initiative led to several key outcomes: the independent availability of LOF, improved agricultural practices, and enhanced farmer group management. The LOF has proven effective as a bioremediation agent, promoting healthier rice growth characterized by vigorous plants, greener leaves, and earlier panicle development. Additionally, the LOF has commercial potential and can be scaled up for broader use. Around 80% of farmers showed active participation and a strong commitment to continuing LOF use, supporting a more sustainable farming system and contributing to the local green economy.